Stereotype of Beauty and Ugliness in Soman Chainani’s The School for Good and Evil - Salsabila, Socha; Assiddiqi, Hasbi; Fauzi, Erfan Muhammad (Institut Agama Islam Negeri Palopo, 2024)
This research analyzes the stereotypes of beauty and ugliness in Soman Chainani’s The School for Good and Evil. This research aims to identify the stereotypes of beauty and ugliness constructed through the characterization of the two main characters, Sophie and Agatha, as well as how the novel challenges and reconstructs traditional expectations of beauty and ugliness. Using a qualitative approach and descriptive analysis methods, this research identifies narrative elements that reinforce and challenge these stereotypes. The research results show that beauty is often associated with good, while ugliness is associated with evil. Sophie, who is described as very physically beautiful, was initially considered good, but later developed into a character full of selfishness. Agatha, who is perceived as ugly, actually displays kindness and strong morality. The novel The School For Good and Evil subverts the traditional stereotype, showing that physical appearance does not always reflect a person's morality. This research uses the theories of Janice Radway and John Cawelti. Radway explains that beauty is often associated with the role of the female hero, while Cawelti discusses the balance between convention and invention in popular works. This research identifies beauty not only through outer beauty such as physical appearance but also inner beauty. Good deeds such as defending, forgiving, helping, giving, and loving are the essence of goodness. With the meaning that inner beauty involves honesty, sincerity, and good deeds that reflect the values of true goodness.